Totally endoscopic periareolar approach for mitral valve repair. First case reported in Peru - Ríos-Ortega, Josías C. (2025)
We present the case of a 39-year-old man with a history of progressive dyspnea. Transthoracic and transesophageal echocardiography revealed severe mitral valve (MV) regurgitation due to P2 flail as well as severe tricuspid valve (TV) regurgitation. The patient underwent surgical treatment, including MV repair and TV annuloplasty, performed through a totally endoscopic periareolar approach. Postoperative evolution was sa